Ovarian Malignancy Prediction by Gatot Purwoto (GP) Score, Risk Malignancy Index (RMI), and Frozen Section in Young Age - Wijaya, Liva (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To know the diagnostic value of a scoring system taken before surgery and frozen section in young-aged patients with suspected malignancy. Using that result, we can also investigate whether frozen section gives additional value to clinical scoring system. Method: This study is a diagnostic test. This study was carried out by accessing RSCM’s medical record from 2006-2011. From 437 patients suspected of ovarian malignancy, we included 157 patients due to age. Result: Diagnostic value of GP score are 77%, 49%, 61%, 68%, 63%, while RMI are 69%, 49%, 58%, 45%, 59%, (sensitivity, specificity, positive predictive value, negative predictive value, and accuracy respectively). Diagnostic value of frozen section in patients with suspected malignancy using GP score >4 are 81.7%, 87.2%, 90.7%, 75.6%, 83%, while in patients with RMI 200 are 81%, 87%, 89%, 77%, 83% (sensitivity, spesificity, positive predictive value, negative predictive value, and accuracy respectively). Conclusion: Gatot Purwoto score and RMI have good diagnostic value in proving malignancy in young age. Its predictive value will be increased by frozen section. [Indones J Obstet Gynecol 2014; 3: 157-161] Keywords: frozen section, gatot purwoto score, ovarian malignancy, RMI, young age